Low serum homoarginine is a novel risk factor for fatal strokes in patients undergoing coronary angiography - Pilz, Stefan; Tomaschitz, Andreas; Meinitzer, Andreas; Drechsler, Christiane; Ritz, Eberhard; Krane, Vera; Wanner, Christoph; Böhm, Bernhard O.; März, Winfried (Stroke, 2011)
BACKGROUND AND PURPOSE: Low serum concentrations of the amino acid homoarginine have been associated with endothelial dysfunction and an increased risk of all-cause and cardiovascular mortality. We aimed to investigate whether homoarginine levels are also associated with fatal strokes and a history of nonfatal cerebrovascular disease. - METHODS: Serum homoarginine was measured in 3305 participants of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study who were referred to coronary angiography at baseline (1997 to 2000) and were followed up with respect to mortality. - RESULTS: During a median follow-up time of 9.9 years, 991 patients died including 61 fatal (ischemic and hemorrhagic) strokes. In a binary logistic regression analysis, the odds ratio (with 95% CI) for fatal stroke per SD of homoarginine was 0.52 (0.37 to 0.73; P<0.001) and remained significant after multivariable adjustments (0.62 [0.42 to 0.91]; P=0.014). For previous cerebrovascular disease events, the multivariable adjusted OR per SD of homoarginine was 0.82 (0.70 to 0.96; P=0.014). - CONCLUSIONS: Low homoarginine levels are a novel risk factor for fatal strokes and are reduced in patients with a history of cerebrovascular disease. Further studies are needed to explore the significance of homoarginine to risk stratification and therapeutic approaches in the prevention of strokes.
Gesehen am 15.12.2022